ABRI di Tengah Paradoks Sosial - Suryo Adi Pramono (Jurnal Ilmu Sosial dan Ilmu Politik, 1998)
Since the Indonesian Army successfully has increased nation-state economic and welfare level (hand in hand with technocrats and foreign capitals), it has to face a new challenge, that is "discontinuity track". This has been remarked by two social paradoxes: (I) global competitions that have expressed in severalhumanity issues (human rights democracy, environment) in front of the existence of national development as political legitimation of the New Order rezim; (2) domestic phenomena; society's struggles in gaining autonomy space in front of centralization of power by the state through various instrumental ways. In this point, the Army has to react those challenges, not only external (toward political, economic, judicial and cultural issues) but also internal ways (self-regulation by scientific understanding and awareness of objectivity on humanity issues). Although facing a tricky real politic canstelation, the Army has to answer those social paradoxes creatively and appropriately, it still wants to get political legitimation for it's power domination. Finally, the main problem is how to formulate the correct answer should be done.